2020
DOI: 10.1016/j.virol.2019.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocapsid proteins from other swine enteric coronaviruses differentially modulate PEDV replication

Abstract: A B S T R A C TPorcine epidemic diarrhea virus (PEDV), transmissible gastroenteritis virus (TGEV) and porcine deltacoronavirus (PDCoV) share tropism for swine intestinal epithelial cells. Whether mixing of viral components during co-infection alters pathogenic outcomes or viral replication is not known. In this study, we investigated how different coronavirus nucleocapsid (CoV N) proteins interact and affect PEDV replication. We found that PDCoV N and TGEV N can competitively interact with PEDV N. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…The interaction between the N and M proteins facilitates the incorporation of the N protein-gRNA ribonucleoprotein complex into the forming viral particle (Kuo et al 2016 ). The N protein is also responsible for inducing endoplasmic reticulum (ER) stress, the prolongation of S phase, and the upregulation of interleukin 8 expression; it promotes the recovery of PEDV from infectious clones; and it increases the production of PEDV RNA and virions (Liwnaree et al 2019 ; Sungsuwan et al 2020 ; Xu et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between the N and M proteins facilitates the incorporation of the N protein-gRNA ribonucleoprotein complex into the forming viral particle (Kuo et al 2016 ). The N protein is also responsible for inducing endoplasmic reticulum (ER) stress, the prolongation of S phase, and the upregulation of interleukin 8 expression; it promotes the recovery of PEDV from infectious clones; and it increases the production of PEDV RNA and virions (Liwnaree et al 2019 ; Sungsuwan et al 2020 ; Xu et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study indicated that mixing of viral components during coinfection altered pathogenic outcomes or viral replication. For example, overexpression of TGEV N increased production of PEDV RNA and virions [ 22 ]; therefore, we inferred that one coinfecting virus might augment the proliferation of the other, leading to more-severe diarrheal disease. Notably, new strains are likely to emerge in cases of coinfection, such as the emergence of recombinant S-INDEL-variant PEDV [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus nucleocapsid phosphoprotein is a multifunctional structural protein; during virion assembly it interacts with the viral membrane and forms complexes with genomic RNA. The coronavirus nucleocapsid phosphoprotein plays an important role in coronavirus transcription and assembly as well as the coronavirus lifecycle [28][29][30][31][32][33][34]. The most potent identified compound, 1-[(2,4-dichlorophenyl)methyl]pyrazole-3,5-dicarboxylic acid], may inhibit any of its multifarious activities and functions during virion assembly; however, detailed studies are needed on the inhibitory effect of these compounds on the interaction of nucleocapsid phosphoprotein with the viral membrane, and formation of complexes with genomic RNA during SARS-CoV-2 transcription and virion assembly.…”
Section: Discussionmentioning
confidence: 99%